Phytochemical screening, in vitro anti-oxidant activity, and in silico anti-diabetic activity of aqueous extracts of Ruellia tuberosa L - Anna Safitri&, Fatchiyah Fatchiyah, Dewi Ratih Tirto Sari, Anna Roosdiana (Journal of Applied Pharmaceutical Science, 2020)
The study aimed to investigate the phytochemical profiles, in vitro antioxidant activity, and in silico molecular docking antidiabetic activity of the aqueous root extracts of Ruellia tuberosa L. The phytochemical qualitative tests revealed the positive detections of tannins, flavonoids, ascorbic acid, and phenolic compounds. Using Liquid chromatography-high-resolution mass spectrometry (LC-HRMS) analysis, 12 compounds were tentatively identified in the extracts. The major compounds were tentatively identified as betaine, daidzein, hispidulin, α-linoleic acid, and 4-coumaric acid. The aqueous root extracts have high antioxidant activity with the IC50 value of 15.2 mg/ml against DPPH free radicals. The major putatively identified compounds were docked to human pancreatic α-amylase protein, to investigate their inhibitory activities to this enzyme. The interaction between betaine, daidzein, and hispidulin in docking with human pancreatic a-amylase showed different binding sites to the protein. In addition, the types of bonds involved were mostly hydrogen and hydrophobic bonds which show the interactions between three ligands and α-amylase. Energy generated from docking between betaine, daidzein, and hispidulin with α-amylase was −137.6, −245.8, and −236.7 cal/mol, respectively. This study concludes that the aqueous root extracts of R. tuberosa L. have prospective as an inhibitor for a-amylase protein and to be used as antidiabetic agent. Further, in vitro and in vivo studies are needed to confirm this work.
Keywords: Ruellia tuberosa L., LC-HRMS, phytochemical screening, DPPH, in silico, α-amylase.